Spatiotemporal shaping of high power laser pulses based on stimulated brillouin scattering - Zhu, Xuehua; Liu, Chuangchuang; Gao, Qilin; Su, Hao; Sun, Sizhou (Frontiers in Physics, 2023)
We proposed and numerically demonstrated the combination of temporal and spatial shaping of high power nanosecond laser pulses based on stimulated Brillouin scattering (SBS) in this paper. With the intensity-dependence characteristic of SBS, the higher intensity parts of the laser beam obtain higher reflectivity, and the incident non-uniform high power laser beam would be well smoothed. A parameter adjustable feedback control loop was used to tailor the output temporal profile by pre-compensating the temporal profile of the input pump. In our numerical simulation, a 3 ns super-Gaussian shaped single-frequency laser pulse with a 527 nm wavelength was used as the pump. And the heavy fluorocarbon FC-70 was chosen as the Brillouin medium. Simulation results show that the laser spatial modulation can be significantly pulled down when the energy efficiency is maintained above 90% in our beam smoothing system with suitable laser intensity. The flat-toped laser pulses both in temporal and spatial domain were demonstrated to be achievable simultaneously. The method proposed here paves a simple and effective way to optimizing the near field pattern and temporal shape of high power laser systems.